Current State and Development Perspectives of the Cultural Routes of the Council of Europe in Istria County - Urošević, Nataša; Legović, Matteo; Tomašković, Meri (Oeconomica Jadertina, 2026)
The paper examines the current state and development prospects of the Cultural Routes of the Council of Europe within Istria County (Croatia). The authors began with the premise that Istria, being a cross-border, multicultural, and multilingual area distinguished by a unique cultural landscape, possesses significant potential for establishing European cultural routes. The research problem arises from the observation that the implementation of the Cultural Routes of the Council of Europe in Istria has remained in its initial stages of development, and that key stakeholders have not yet fully recognized the strategic potential of enhancing the region’s distinctive heritage through the establishment of transnational cultural routes. The research methodology employed a qualitative case study approach, incorporating both desk and field research, which involved interviews with representatives from key stakeholders. After conducting a literature review, this research presents a case study of Istria County. The analysis focuses on identifying existing challenges, developmental prospects, and recommended strategic measures concerning the implementation of the Cultural Routes of the Council of Europe in the region. The findings indicate that European thematic cultural routes, recognized as the most accessible and cost-efficient forms of cultural tourism, can play a crucial role in reinforcing local identities and promoting sustainable economic development in the region. Istria County, as a cross-border area, has the potential to promote cultural routes as a model for the valorisation of shared European heritage and core European values.
Keywords: cultural routes, Council of Europe, transborder regions, European heritage, Istria